2020
DOI: 10.21470/1678-9741-2019-0215
|View full text |Cite
|
Sign up to set email alerts
|

Mid-Term Outcome after Tricuspid Valve Replacement

Abstract: Objective To evaluate the mid-term survival rate after tricuspid valve replacement (TVR). Methods We retrospectively studied 110 consecutive patients who underwent TVR from January 2007 to November 2017. A survival analysis was performed with the Kaplan-Meier method and the log-rank test. Results The median survival was 65.81 months. Mean age was 50 (range 39 to 59) years. Forty-eight patients (43.6%) were male, and 62 patients (56.4%) were f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
(53 reference statements)
0
2
0
Order By: Relevance
“…Around 0.5 -1% of these patients can also develop refractory post-cardiotomy cardiogenic shock not responsive to these measures, in which case, accelerated support such as ECMO is needed [39,40]. Patients with pre-operative right ventricular dysfunction are at higher risk of requiring intracardiac support, such as IABP and Impella, due to low cardiac output associated with right ventricular dysfunction [41]. In our study, patients who underwent open TVR were more likely to require an intra-aortic balloon pump (IABP) and Impella (although statistically insignificant) than TTVR.…”
Section: Discussionmentioning
confidence: 99%
“…Around 0.5 -1% of these patients can also develop refractory post-cardiotomy cardiogenic shock not responsive to these measures, in which case, accelerated support such as ECMO is needed [39,40]. Patients with pre-operative right ventricular dysfunction are at higher risk of requiring intracardiac support, such as IABP and Impella, due to low cardiac output associated with right ventricular dysfunction [41]. In our study, patients who underwent open TVR were more likely to require an intra-aortic balloon pump (IABP) and Impella (although statistically insignificant) than TTVR.…”
Section: Discussionmentioning
confidence: 99%
“…In Table 4 , intraoperative risk factors including ACPBT and cTVR were new predictors for postoperative MODS besides CCr, BUN/BCr and PD, we also found PD (OR 4.69) and cTVR (OR 3.69) were the high-risk factors for postoperative MODS. Researchers showed surgical intervention for severe tricuspid valve disease is only indicated in symptomatic patients, or who have severe comorbidities [ 53 , 54 ]. Sharma et al reported that right ventricular failure is related to nearly 40% kidney failure and has an increased mortality risk after TVR [ 55 ].…”
Section: Discussionmentioning
confidence: 99%